Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst

Selective, bifunctional Cu-WOx/Al2O3 catalyst for hydrodeoxygenation of fatty acids - Janampelli, Sagar; Sethia, Govind; Darbha, Srinivas (Catalysis Science & Technology, 2020)
Selective hydrodeoxygenation of oleic acid (OA; in a batch reactor, at 300 degrees C, 30 bar H-2 pressure, reaction time of 1 h and reactant-to-catalyst weight ratio of 2 g OA/0.2 g) forming n-octadecane in yields as high as 93% over a non-noble metal, sulfur-free, bimetallic Cu-WOx/Al2O3 catalyst is reported for the first time. Several Cu-WOx/Al2O3 compositions were prepared by a sequential wet-impregnation method and evaluated. A catalyst with 10 wt% Cu and 4 wt% W enabled the highest activity and selectivity. Upon adding WOx, the amount of moderate and strong acid sites increased and more Cu in the catalyst was in reduced electron-rich metallic (Cu-0) state. The crystallite size and dispersion of Cu were little affected. WOx promoted the fatty acid hydrodeoxygenation activity of Cu. While a monometallic Cu catalyst (10Cu/Al2O3) yielded n-octadecane and n-heptadecane along with high amounts of intermediate octadecanol and octadecanal products, the bimetallic catalyst (10Cu-4WO(x)/Al2O3) gave mainly n-octadecane. Acidity and the high amount of reduced Cu-0 species are responsible for the high catalytic hydrodeoxygenation performance of this bimetallic catalyst.

Selective deoxygenation of fatty acids to fuel-range hydrocarbons over Pt-MOx/ZrO2 (M = Mo and W) catalysts - Janampelli, Sagar; Darbha, Srinivas (Catalysis Today, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A comparative catalytic activity study of Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> for deoxygenation of oleic acid (OA) forming fuel-range, linear hydrocarbons is reported. These catalysts (with 4 wt% Pt and 8 wt% Mo or W) were prepared by a sequential wet-impregnation method and characterized for the structural and electronic properties. Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> showed higher catalytic activity than Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. Hydrodeoxygenation was the selective pathway over these bifunctional catalysts yielding n-octadecane. High conversion of OA was achieved at 200 °C itself. On the contrary, monometallic Pt/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was weakly active. It was selective mainly toward decarboxylation/decarbonylation producing n-heptadecane. Higher amounts of Pt and metal oxide in reduced forms are responsible for the high hydrodeoxygenation activity and selectivity of these reusable, bimetallic catalysts.